Literature Review: Prospek Peningkatan Suku Bunga terhadap Nilai Perusahaan dan Return Saham - Rihfenti Ernayani; Muhammad Imam Asnawi; Natalia Reyne Lumentah; Irwan Moridu; Winda Lestari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The existence of the capital market in Indonesia has an important role in economic development. There are important factors that investors pay attention to, namely the condition of interest rates and stock returns, and these affect the value of the company. The research method is in the form of a literature study by reviewing various related studies recorded in Mendeley references and Google Schoolars both nationally and internationally. The results of this study were analyzed and used as material for discussion to determine answers to problems regarding the relationship between risk mitigation and rescue procedures in the people's credit system. All ideas from each study provide information about the methodologically desirable theory of the study being analyzed. The results explain that there is a positive relationship between interest rates and stock returns on firm value and it can influence investors to buy shares in the company. Keywords: Firm Value, Stock Returns, Interest Rate